Optimization of Ale-Type Craft Beer Through the Addition of Cañihua Malt (Chenopodium pallidicaule) and Aguaymanto Juice (Physalis peruviana) Using a D-Optimal Experimental Design - Luz Maria Paucar-Menacho; Rebeca Salvador-Reyes; Wilson Daniel Simpalo-Lopez; Alicia Lavado-Cruz; Anggie Verona-Ruiz; Jordy Campos-Rodriguez; Katherine Acosta-Coral; Williams Esteward Castillo-Martinez; William López-Rodriguez; Soledad Quezada-Berrú (Beverages)
The global growth of the craft beer market has driven the use of native ingredients to improve the sensorial and nutritional qualities of the product. This study investigated the optimization of an Ale-type craft beer from Pilsen malt (PM) with the addition of cañihua malt (CM) and aguaymanto juice (AJ), using a D-optimal experimental design. The independent variables were CM (5–25%) and AJ (5–15%), which influenced the physicochemical, technological, and sensorial attributes of the beer. The results show that CM and AJ improve the physicochemical properties of the beer, such as foam stability and alcohol content, while maintaining comparable levels of specific gravity, turbidity, and bitterness with the control sample. The addition of AJ significantly altered the physicochemical profile of the beer, in particular by reducing pH and increasing acidity. Sensory analysis revealed positive consumer acceptance, with favorable evaluations of aroma, appearance, and body, particularly in samples containing moderate levels of CM and AJ. In addition, consumer purchase intention was high for these formulations. Optimization through the desirability function determined that the ideal ingredient concentrations were 74.52% PM, 15.55% CM, and 8.93% AJ. Within the ranges studied, it is concluded that the addition of CM and AJ successfully produced a craft beer with notable nutritional benefits and high sensory acceptability.